When Words Fail: Exploring Speaking Anxiety Among ESL Learners - Tampubolon, Muhammad Ahsan (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This study examined the speaking anxiety levels and sources among 130 English as a Second Language (ESL) students at Universitas Pamulang, across basic and intermediate courses. Speaking competence is crucial in today's globalized world, yet anxiety often hinders learners' confidence and participation. Using a quantitative survey, the adapted